The Proposed ICD-11 Gender Incongruence of Childhood Diagnosis: A World Professional Association for Transgender Health Membership Survey - Winter, Sam; De Cuypere, G.; Green, J.; Kane, R.; Knudson, G. (Springer New York LLC, 2016)
© 2016 Springer Science+Business Media New YorkICD-11 (the eleventh edition of the World Health Organization International Statistical Classification of Diseases and Related Health Problems) is due for approval in 2018. For transgender health care, the most important proposals for ICD-11 are as follows: (1) the five ICD-10 diagnoses (most notably Transsexualism and Gender Identity Disorder of Childhood) currently in Chapter 5 (Mental and Behavioural Disorders) will be replaced by two Gender Incongruence diagnoses, one of Adolescence and Adulthood and the other of Childhood (GIC), and (2) these two diagnoses will be located in a new chapter provisionally named Conditions Related to Sexual Health. Debate on the GIC proposal has focused on whether there should be a diagnosis for young children exploring their identity and has drawn on a number of arguments for and against the proposal. The World Professional Association for Transgender Health conducted a survey to examine members’ views concerning the GIC proposal, as well as an alternative framework employing non-pathologizing Z Codes. The survey was completed by 241 (32.6 %) out of 740 members. Findings indicated an even split among members regarding the GIC proposal (51.0 % [n = 123] opposing and 47.7 % [n = 115] supporting the proposal). However, non-US members were overall opposed to the proposal (63.9 % [n = 46] opposing, 36.1 % [n = 26] supporting). Across the sample as a whole, and among those expressing a view about Z Codes, there was substantial support for their use in healthcare provision for children with gender issues (35.7 % [n = 86] of the sample supporting vs. 8.3 % [n = 20] rejecting).